Genome-Wide Association Study of Salinity Tolerance During Germination in Barley (Hordeum vulgare L.) - Mwando, Edward; Han, Yong; Angessa, Tefera Tolera; Zhou, Gaofeng; Hill, Camilla Beate; Zhang, Xiao-Qi; Li, Chengdao (Frontiers in Plant Science, 2020)
Barley seeds require the ability to germinate and establish seedlings in saline soils in the Mediterranean type of climates, which are characterised by hot and dry summers. Despite being one of the major cereal crops, barley has few reported quantitative trait loci (QTL) and candidate genes underlying salt tolerance at the germination stage. Breeding process targeting salinity tolerance at germination requires a detailed understanding of genetic loci and alleles presented in current breeding germplasms. In this study, we investigated seed germination-related traits under control and salt stress conditions based on 350 diverse barley accessions. A Genome-wide association study (GWAS) was performed using ~35,000 genetic markers to detect marker-trait associations (MTA) and the underlying candidate genes for salinity tolerance during germination. Thirteen loci containing forty-eight significant salt-tolerance associated markers were detected on all chromosomes except 4H, and 12 genes belonging to 11 family functions underlying the MTAs predicted. Our results provide new genetic resources and information to help improve salt tolerance at germination of future barley varieties via genomic and marker-assisted selection and open up avenues for further functional characterization of the identified candidate genes.